2011
DOI: 10.1111/j.1600-0846.2010.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the visualization and quantification of internal skin elasticity by ultrasound imaging

Abstract: These findings support the validity and sensitivity of the TSI method to assess the elasticity of various layers of skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The values measured tend to deviate greatly because of the free-hand technique. Moreover, skin and subcutaneous tissue strains can be affected by other factors such as age (Osanai et al 2011). In consideration of the aforementioned problems and confounding factors, these measurements should be interpreted cautiously at present.…”
Section: Limitationsmentioning
confidence: 98%
“…The values measured tend to deviate greatly because of the free-hand technique. Moreover, skin and subcutaneous tissue strains can be affected by other factors such as age (Osanai et al 2011). In consideration of the aforementioned problems and confounding factors, these measurements should be interpreted cautiously at present.…”
Section: Limitationsmentioning
confidence: 98%
“…The various solitary skin lesions were imaged in B mode (2 Dimensional image) without colour Doppler at 14 MHz because it was the maximum frequency commercially available and FDA approved for human use by the vendor in the United States when this study was performed, and it is within the range previously reported as acceptable for the task. 5,33,34 At this frequency, the maximum depth of penetration is 40 mm. In this study, the frame of view for the ultrasound transducer was kept between 7.5 and 10 mm.…”
Section: Methodsmentioning
confidence: 99%
“…[28][29][30][31] High-frequency ultrasound also offers an intriguing analog to traditional skin palpation; it can provide information about the stiffness of a lesion at and below the skin surface, using the functional image processing technique known as ultrasound elastography (USE). [32][33][34][35][36][37] In strain elastography, a single relatively small compression made by the transducer allows determination of the rate of change in displacement of tissue as a function of distance from the transducer (strain). The strain value is an indirect measurement of elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, except for a few studies [13,17,20,21], elastographic parameters of normal skin have not been studied to date, and no published reference values for skin strain have been identified thus far. Moreover, most previous cutaneous elastography studies were relatively small observational studies or analyses of case series.…”
Section: Elastographic Parameters Of Normal Skin and Their Determinantsmentioning
confidence: 99%
“…The dermis is characterized by higher strain than subcutaneous tissue [21]. Furthermore, the latter is not homogeneous in terms of its elastographic characteristics, due to the presence of stiffer connective tissue septa, and more elastic adipose tissue lobes, blood vessels and nerve fibers [21].…”
Section: Elastographic Parameters Of Normal Skin and Their Determinantsmentioning
confidence: 99%